Nanoclay Reinforced Ternary Blends Based on Biodegradable Polymers for Drug Delivery Application. (7th September 2022) - Ali, Mohsin; Mir, Sadullah; Abid, Obaid-Ur-Rahman; Yawer, Mirza Arfan; Ullah, Ihsan
Abstract : In this study, ternary blends based on chitosan, polyvinyl alcohol, and polyethylene glycol reinforced with organically modified montmorillonite (nanoclay) clay were synthesized. These ternary blends were evaluated as transdermal drug delivery patches using tramadol as a model drug. The FTIR study showed interaction among important functional groups and compatibility among the mixing components. Among drug-loaded formulations, composite MA12 shows maximum thermal stability with 27.9% weight residue at 540°C. The prepared formulations exhibited crystalline nature as observed by XRD analysis. SEM studies revealed that there are no gaps and cracks in prepared films and nanoclay was found dispersed in the formulations. The swelling ratio was higher in pH 1.2 as compared to pH 4.5 and pH 6.8 buffers, and there was an increase in swelling with an increase in PVA concentration. Moreover, the drug release test performed in phosphate buffer pH 6.8 showed that tramadol release from nanocomposite films increases with an increase in PEG concentration. Permeation studies indicated that the rate of permeation increased with a decrease in PVA concentration. The permeation rate was found to be higher for samples without nanoclay. The overall results suggest nanocomposite films as excellent candidates for transdermal drug delivery application.